2021
DOI: 10.1007/s13312-021-2302-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Guillain-Barré Syndrome in 108 Children

Abstract: Objectives To review the clinical outcome and electrophysiologic characteristics of children with Guillain-Barré syndrome (GBS) from Eastern India. Methods The hospital records of the children aged less than 12 years with a final diagnosis of GBS at our hospital from November, 2015 to December, 2018 were reviewed. Disabilities were assessed at 8-weeks and 6-month follow-up using Hughes scale (0–6). Results Demyelinating variety in 57 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…The clinical and demographic characteristics of our study cohort were similar to the previous studies. There was a significant male preponderance (62.8%) in our study population, which has been described in earlier studies also 8,9 . We found that the axonal variant of GBS was preceded by gastrointestinal infections and the demyelinating variant by upper respiratory tract infections, similar to the previous reports 9,10 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The clinical and demographic characteristics of our study cohort were similar to the previous studies. There was a significant male preponderance (62.8%) in our study population, which has been described in earlier studies also 8,9 . We found that the axonal variant of GBS was preceded by gastrointestinal infections and the demyelinating variant by upper respiratory tract infections, similar to the previous reports 9,10 …”
Section: Discussionsupporting
confidence: 92%
“…8,9 We found that the axonal variant of GBS was preceded by gastrointestinal infections and the demyelinating variant by upper respiratory tract infections, similar to the previous reports. 9,10 The most common clinical presentation observed in our study was paraparesis. The median (IQR) time from onset to peak weakness was 4 (3, 6) days, which was comparable with other studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[ 37 ] In studies from India, need for artificial ventilation, delay in independent walking, inexcitable nerves on conduction testing, and axonal subtype have been associated with poorer outcomes. [ 38 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…Two of the identified studies came from the same centre and the study with the shorter duration of study period was excluded. The relevant data is summarized in Supplementary Table 3 [9][10][11][12][13][25][26][27][28][29][30][31][32].…”
Section: Literature Reviewmentioning
confidence: 99%